IMPLEMENTASI KEBIJAKAN PERIZINAN PERIKANAN TANGKAP DI KABUPATEN PEMALANG - Naibaho, Muhammad Arfan; ., Teguh Yuwono (Journal of Politic and Government Studies, 2017)
The system of regional autonomy provided the authority to manage the affairs of their own region. As well as with the implementation of the licensing policy fisheries catch in Pemalang. It is related to the discussion of the implementation of the licensing policy fisheries catch in Pemalang are not yet running optimally so that cause problems in practice. This research aims to analyze the process of capture fisheries licensing policy implementation in Kabupaten Pemalang, analyzing the factor endowments and a obstacle to implementation.The methods used in this study is a mixed method research, where the qualitative and quantitative data collection done in one time. In obtaining the data, researchers conduct interviews at the Office of the Department of marine and Fisheries of Central Java province, Coastal Asemdoyong fishing port, Port Services Unit Pekalongan, Regional Headquarters of HNSI in Pemalang, and distributed questionnaire to fisherman in the region of Pemalang district. Researchers also use secondary data from data documents about licensing policy fisheries catch and other literature sources such as books and journals.The results showed that the capture fisheries licensing organization of bringing about change in terms of the performance of the Government as well as the changes to people behavior. The purpose of the capture fisheries licensing policies to accelerate and simplify the licensing process for the fishermen have not been fully achieved. The large number of requirements that must be completed and the length of the procedure of licensing management service on an issue that has often complained of by the fishermen. In addition a transitional licensing fisheries catch which was originally located in the County and then redirected to the province is also one of the constraints given a distance far enough for the fishermen who live in the Regency of Pemalang. The Government is required to continue to evaluate the existence of licensing policy fisheries catch in order to always provide real benefits for fishermen and fishermen would be more active in participating in its implementation.Recommendations are provided to the Government was re-evaluating the capture fisheries licensing policy implementation to match the needs of fishermen, and organizer of the policy must be able to accommodate the interests of various sectors, ranging from Government, community, private sectors, and so created the effectiveness of implementation of policies on licensing fishing catch.Keywords: Policy Implementation, License, Capture Fisheries, Services